Genetic variability, heritability and genetic advance in litchi (Litchi chinensis) - MARBOH, E S; GUPTA, A K; GYANESH, K; SINGH, M; SINGH, A; NATH, V (The Indian Journal of Agricultural Sciences, 2018)
Litchi (Litchi chinensis Sonn.) is one of the most important subtropical fruit crops of the world. Improvement in this crop is constrained by its narrow genetic base, which is a major bottleneck in reaching the desired objectives. Studies on the nature and extent of genetic variability are highly relevant to yield information that can be useful for genetic improvement programmes. In the present study, 22 litchi genotypes including three new varieties were assessed for the variability, heritability and genetic advance and principal component analysis on the basis of 13 quantitative fruit traits. High phenotypic and genotypic coefficients of variation were recorded for pulp weight (32.86 and 31.11%), seed weight (30.56 and 27.93%), peel thickness (25.07 and 20.21%), pulp thickness (24.79 and 22.22%) and fruit weight (22.65 and 21.17%).The heritability and genetic advance were found maximum for fruit yield/plant. High heritability coupled with high genetic advance was recorded for fruit weight, fruit length, fruit width, pulp weight, pulp thickness, seed weight, peel thickness, peel weight, seed width (y-axis) and yield/plant, indicating ample scope of improvement for these traits through selection. From PCA and variability estimates, fruit weight, pulp weight, peel weight, peel thickness, seed weight and seed size were identified as important traits for identifying high-yielding genotypes.